The hardness and chemical changes in demineralized primary dentin treated by fluoride and glass ionomer cement - Gisele Fernandes DIAS; Ana Cláudia Rodrigues CHIBINSKI; Fábio André dos SANTOS; Viviane HASS; Fabiana Bucholdz Teixeira ALVES; Denise Stadler WAMBIER
Abstract Background Fluoride plays an important role in the control of dental caries. Aim To evaluate the chemical exchange between restoration of glass ionomer cement of high viscosity (GIC) and primary dentin with application of sodium fluoride (NaF) 2% through changes in hardness from uptake of calcium, phosphate and fluoride. Material and method Class I cavities were prepared in 40 sound primary molars, and the sample was divided into two groups (n=20) according to dentin condition: sound (1) and demineralized (2). Sub-groups (n=10) were formed to investigate the isolated action of the GIC or the association with NaF (F). This in vitro study examined the chemical exchange under two conditions, sound and demineralized dentin (pH cycling), to simulate the occurrence of mineral loss for the caries lesion. G1 and G2 received GIC restoration only; groups G1F and G2F received NaF before GIC restoration. The specimens were prepared for Knoop hardness test and micro-Raman spectroscopy. A two-way ANOVA test (α = 0.05) was used for statistical analysis. Micro-Raman data were qualitatively described. Result Increased hardness was observed in all the sites of direct contact with GIC in sound and demineralized dentin for all groups (p<0.001); no difference was observed in microhardness after application of NaF (p>0.05). In the evaluation of micro-Raman, direct contact between GIC and dentin for sound and demineralized dentin resulted in increased peaks of phosphate. Conclusion The exchange between GIC and demineralized dentin may induce changes of mechanical properties of the substrate, and uptake of mineral ions (phosphate) occurs without the influence of NaF.